A Comparative Study on the Confinement Models of High-Strength Steel Fiber Concrete - Nur Fithriani F. Cholida; Antonius; Lintang Enggartiasto (Journal of the Civil Engineering Forum, 2022)
Since the last four decades, the behavior of concrete contains of steel fiber, or often called steel fiber concrete, with a wide range of compressive strength has been carried out. Generally, the results of the experimental program produced a material which has a more ductile compared with normal concrete or concrete without fiber. Due to the ductility properties of the material, it is very suitable for use as an earthquake-resistant structural material. At the same time, the behavior of high-strength steel-fiber concrete has also investigated, one of which is about confined high-strength steel-fiber concrete. Analytical models of confined high-strength steel fiber concrete have been developed in various preliminary studies, with their characteristics derived based on the experimental results. Therefore, this research evaluated the models of confined high-strength steel-fiber concrete proposed by Mansur et al., Hsu and Hsu, and Paultre et al. The evaluation includes stress-strain behavior, strength enhancement of confined concrete (f'cc/f'co) or K value, the increase in confined concrete strain (ε'cc/ε'co), and strain of confined concrete when the stress has dropped by 50 percent against its unconfined strain (εcc50/εc50). The comparison method was carried out using a statistical approach and stress-strain simulation. Evaluation results showed significant predictive differences in confinement models in terms of post-peak behavior and parameters ε'cc/ε’co and εcc50/εc50. Prediction of confinement models on the value of f'cc/f’co to the experimental results has a coefficient of variation above 10%. The result further showed that a modified model of confined high-strength steel-fiber concrete was proposed and able to simulate the stress-strain behavior.